2017
DOI: 10.1175/ei-d-15-0045.1
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization Impacts on the Summer Heavy Rainfall Climatology over the Eastern United States

Abstract: The relationship between rainfall characteristics and urbanization over the eastern United States was examined by analyzing four datasets: daily rainfall in 4593 surface stations over the last 50 years (1958–2008), a high-resolution gridded rainfall product, reanalysis wind data, and a proxy for urban land use (gridded human population data). Results indicate that summer monthly rainfall amounts show an increasing trend in urbanized regions. The frequency of heavy rainfall events has a potential positive bias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(51 citation statements)
references
References 39 publications
2
43
0
3
Order By: Relevance
“…This observation does not necessarily mean that rainfall over downwind region is lower than that at Kanpur core region, mainly because IITK might not be a representative downwind site of peak urban‐induced rainfall modification. Recent studies have illustrated that the urban‐induced effect on rainfall are manifested 30–80 km downwind of the cities in Unites States and India (Niyogi et al, ; Kishtawal et al, ). Therefore, we also have also used the TRMM‐PR data set to create climatological mean spatial distribution of rainfall events around the greater Kanpur and check for modification in downwind rainfall.…”
Section: Resultsmentioning
confidence: 99%
“…This observation does not necessarily mean that rainfall over downwind region is lower than that at Kanpur core region, mainly because IITK might not be a representative downwind site of peak urban‐induced rainfall modification. Recent studies have illustrated that the urban‐induced effect on rainfall are manifested 30–80 km downwind of the cities in Unites States and India (Niyogi et al, ; Kishtawal et al, ). Therefore, we also have also used the TRMM‐PR data set to create climatological mean spatial distribution of rainfall events around the greater Kanpur and check for modification in downwind rainfall.…”
Section: Resultsmentioning
confidence: 99%
“…There have been a growing number of recent studies that suggest the role of the impervious surface of urban areas in modulating rainfall. [16][17][18][19] For example, Shepherd et al 17 using Tropical Rainfall Measuring Mission (TRMM) found a significant increase in warm season rainfall, 30-60 km downwind of major metropolitan cities in the southern United States. Similarly, Niyogi et al 19 find that summer monthly rainfall amounts display an increasing trend in urbanized regions especially in the northeastern and mid-western United States.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] For example, Shepherd et al 17 using Tropical Rainfall Measuring Mission (TRMM) found a significant increase in warm season rainfall, 30-60 km downwind of major metropolitan cities in the southern United States. Similarly, Niyogi et al 19 find that summer monthly rainfall amounts display an increasing trend in urbanized regions especially in the northeastern and mid-western United States. In examining the spatio-temporal patterns of warm season rainfall over Atlanta, McLeod et al 20 found that the increase in the early evening rainfall coincided with the warming of the surface temperature from the urban heat island effect, which in turn increased convective forcing.…”
Section: Introductionmentioning
confidence: 99%
“…The built‐up land areas contain all the cities and the major settlements intensively. Many studies also chose population density as a criterion for separation of urban from rural areas (e.g., Kishtawal et al ., ; Singh et al ., ; Niyogi et al ., ). The spatial patterns of urban areas are consistent with that of the population density; that is to say urban areas are the areas with high population density (Figure ).…”
Section: Datamentioning
confidence: 99%